2022
DOI: 10.1037/pspp0000387
|View full text |Cite
|
Sign up to set email alerts
|

A sociocultural norm perspective on Big Five prediction.

Abstract: The Big Five predict numerous preferences, decisions, and behaviors—but why? To help answer this key question, the present research develops the sociocultural norm perspective (SNP) on Big Five prediction—a critical revision and extension of the sociocultural motives perspective. The SNP states: Agreeableness, Extraversion, and Conscientiousness predict outcomes positively if those outcomes are socioculturally normative. Openness, by contrast, predicts outcomes negatively if they are socioculturally normative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 89 publications
(165 reference statements)
2
25
0
Order By: Relevance
“…Second, evidence for the SMP is not limited to religiosity, but extends to partner preferences (Gebauer, Leary, & Neberich, 2012) and to prosociality (Gebauer, Sedikides, et al, 2014). Finally, the SMP has recently been tested in experimental settings (Eck & Gebauer, 2020a, 2020b). Due to the specific experimental setup, it was impossible that the criteria (e.g., preferences for Chinese characters) differentially exerted an effect on personality as a function of the (experimentally manipulated) normative preferences of those characters in one’s culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, evidence for the SMP is not limited to religiosity, but extends to partner preferences (Gebauer, Leary, & Neberich, 2012) and to prosociality (Gebauer, Sedikides, et al, 2014). Finally, the SMP has recently been tested in experimental settings (Eck & Gebauer, 2020a, 2020b). Due to the specific experimental setup, it was impossible that the criteria (e.g., preferences for Chinese characters) differentially exerted an effect on personality as a function of the (experimentally manipulated) normative preferences of those characters in one’s culture.…”
Section: Discussionmentioning
confidence: 99%
“…As we describe later on, those approximated BFI-2 facets yielded results comparable to our BFI results (see Footnote 16). Finally, we had the opportunity to analyze data of a set of Amazon Mechanical Turk (MTurk) studies, which include our religiosity measure (see Study 1 Method section) and the BFI-2 (Eck & Gebauer, 2020a). The present research is the first that used those studies’ data to investigate how much religiosity variance the BFI-2 facets explain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sociocultural norm perspective predicts that several of Big Five personality traits are differentially linked to numerous preferences, decisions, and behaviors according to what is socioculturally normative (Eck & Gebauer, 2022). Prior research has not, however, specifically addressed how each of the Big Five traits correspond to conforming to the average personality profile within one's country.…”
Section: Dispositional Traits and Conformitymentioning
confidence: 99%
“…Our study was designed to fill some specific knowledge gaps in the social and personality sciences. First, while prior evidence shows that some personality traits are linked to motivations to fit in or deviate away from others (Bleidorn et al, 2016; Eck & Gebauer, 2022; Gebauer et al, 2020), it is currently unknown how each Big Five personality trait may correspond to conforming to county-level standards in personality profiles. Furthermore, although many studies have revealed links between culture and mean levels of personality traits (Church, 2016), it is currently unknown how culture may be associated with variation in county-level personality profile conformity.…”
Section: Introductionmentioning
confidence: 99%